Improving weaned piglet performance by supplementing with a probiotic lactic acid bacterium - Stoppani, Constanza Laura (2025)
Objective: Evaluate the impact of Lactobacillus salivarius (Ligilactobacillus salivarius comb nov) DSPV014C supplementation on weaned piglet growth performance through its effect on the modulation of microbiota and intestinal morphology. Materials and methods: In a randomized complete block design, 20 piglets were divided into two groups, probiotic group (PG) supplemented with L salivarius DSPV014C and control group (CG) without supplementation, at 28 days of age and kept under study for 42 days. Feces were sampled weekly to evaluate microbial population dynamic and diversity, evenness, and richness indexes. To calculate average daily gain, average daily feed intake, and feed conversion ratio (FCR), piglets were weighed and feed consumption was registered weekly. Three piglets from each group were euthanized on day 42 and samples of the small intestine taken to evaluate intestinal morphology through villi length, crypt depth, and the ratio of the two (V/C). Results: Lactobacillus salivarius was recovered in feces from PG on day 7 demonstrating its ability to reach the intestine. Microbiota modulation differed resulting in different profiles between groups; PG exhibited higher diversity (P = .01) and richness (P = .07) indexes, while no differences were observed for evenness. The PG showed lower FCR and longer villi length and higher V/C ratio than CG (P < .05). Implications: The FCR improved in PG compared to CG piglets, which could be explained by an increase in the digestion and absorption capacity due to longer intestinal villi and differential modulation of the intestinal microbiota with higher richness and diversity indexes.